2013
DOI: 10.1007/s00335-013-9472-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain-expressed imprinted genes and adult behaviour: the example of Nesp and Grb10

Abstract: Imprinted genes are defined by their parent-of-origin-specific monoallelic expression. Although the epigenetic mechanisms regulating imprinted gene expression have been widely studied, their functional importance is still unclear. Imprinted genes are associated with a number of physiologies, including placental function and foetal growth, energy homeostasis, and brain and behaviour. This review focuses on genomic imprinting in the brain and on two imprinted genes in particular, Nesp and paternal Grb10, which, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…While many studies have characterized imprinting in early development and its functional role, for example, in placental function and fetal growth, our results shed light on patterns of imprinting in adults, which have been shown to have functional consequences as well (Ubeda and Gardner 2011;Dent and Isles 2014). The patterns of imprinting discovered in this study provide additional empirical data for evaluating theories for evolutionary causes for imprinting (Bartolomei and Ferguson-Smith 2011;Patten et al 2014).…”
Section: Discussionmentioning
confidence: 54%
“…While many studies have characterized imprinting in early development and its functional role, for example, in placental function and fetal growth, our results shed light on patterns of imprinting in adults, which have been shown to have functional consequences as well (Ubeda and Gardner 2011;Dent and Isles 2014). The patterns of imprinting discovered in this study provide additional empirical data for evaluating theories for evolutionary causes for imprinting (Bartolomei and Ferguson-Smith 2011;Patten et al 2014).…”
Section: Discussionmentioning
confidence: 54%
“…Recent work has also shown that paternal deletion of Grb10, which is expressed from the paternal allele in a subset of neurons from alternative promoter(s), is associated with hyper-aggression and increased social dominance in mice (Garfield et al, 2011). Finally, a maternally expressed gene, Nesp (Gnas), which encodes a protein involved in neuro-excretory function, is associated with novel exploration behavior and has been observed to have striking overlap in expression with Grb10 in the brain (Dent and Isles, 2014;Plagge et al, 2005).…”
Section: Fig 2 Imprinting Mechanisms (A) the Insulator Model Is Bestmentioning
confidence: 99%
“…Imprinted DMRs can influence expression by acting as methylation-sensitive insulators (such as the paternally methylated H19 DMR) (Hark et al, 2000) or alternatively as promoters of ncRNA which recruit epigenetic regulators (such as the maternally methylated DMR associated with Kcnq1ot1) (Lee et al, 1999). Imprinted genes have been shown to influence not only early embryonic development and placental function, but impact on behavior and metabolic adaption later in life (Constância et al, 2004;Madon-Simon et al, 2014;Dent and Isles, 2014). Therefore it is likely that genome-wide disruption to imprinted gene expression is the principal cause of defects observed in methylation-deficient knockout mice (Kaneda et al, 2004).…”
Section: Imprinted Genesmentioning
confidence: 99%